An impact of CMV and HHV-6 reactivation on the course of early period after hematopoietic stem cell transplantation in patients with hematologic malignancies - T. V. Antonova; M. S. Nozhkin; О. Е. Pobegalova; О. V. Gorchakova; N. V. Sabadash; D. A. Lioznov (Журнал инфектологии, 2023)
Objective. To assess the impact of CMV and HHV-6 reactivation on the course of early post-transplant period in patients with hematologic malignancies.   Materials. Retrospective analysis of medical records of 339 patients with hematologic malignancies who received hematopoietic stem cell transplantation (HSCT) was performed, and markers of CMV and HHV-6 infections were detected (specific IgG, EIA). Blood and other materials from HSCT recipients were tested (PCR) for viral DNA in early post-transplant period (up to Day 100).   Results. Reactivation of viral infections after HSCT was discovered in 177 patients (52,2 %): CMV-infection was detected in 23 %, HHV-6 in 17,4 %, CMV+HHV-6 in 11,6 % of HSCT recipients. CMV DNA was predominantly identified in blood, while HHV-6 DNA was more frequently discovered in GIT mucosa and bone marrow. 40 % of 99 patients with HHV-6 reactivation had concomitant CMV+HHV-6 reactivation. In this group, the clinical manifestation of infections was registered significantly more frequently. Febrile neutropenia was more frequent in HSCT recipients with CMV reactivation, sepsis and graft hypofunction were diagnosed more frequently in presence of HHV-6 and predominantly HHV-6+CMV infections. The direct correlation (using Spearman’s method) between CMV and HHV-6 reactivation and terms of leukopoiesis recovery, engraftment terms, and transplant hypofunction was revealed. An impact of herpetic infections reactivation on the graft hypofunction and late recovery of leukopoiesis was confirmed using the logistic regression; its impact on the chimerism was revealed. In 72 % of cases, the graft failure in early post-transplant period occurred in patients with herpetic infections reactivation.   Conclusion. HHV-6 and CMV reactivation in the early period after HSCT correlates with terms of leukopoiesis recovery, contributes to development of complications, and is an additional factor aggravating the course of the post-transplant period.